Educator: To The Awesome Educators and Students - Febri Mira Rizki; Chandra Halim (International Journal Labs, 2023)
Literacy has spread throughout Indonesia, especially in the world of education. This program was increasingly promoted after the Independent Curriculum was hammered by the government. Strengthening literacy competencies in madrasahs is also accelerating because educators are working so that this knowledge can be smoothly transmitted to students for their intake. Both in terms of theory and terms of practice. One of the products born in the name of literacy in Indonesian language learning is work. In one writing skill, for example: poetry, short stories, articles, essays, reviews, rhymes, prose, etc. With the work of educators and students, literacy in madrasas will be increasingly felt. This activity will make the madrasah trusted by the community because the ability of its educators can advance their students. So that from whatever point of view the madrasah is monitored it will shine.